2017
DOI: 10.1080/09638288.2017.1331379
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of immigrant women on long-term sick leave and their experience of dignity

Abstract: The immigrant women maintained and protected their dignity by finding strength, pride, and self-worth in their religion and through their family-members' affection. Taking responsibility for themselves and others and experiencing fellowship and equality with other women, they enhanced their dignity during their rehabilitation process. The caring attitudes and behavior of some healthcare personnel promoted patient dignity. They also gained hope and dignity by experiencing goodness, cultural competence, and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It echoed previous research, which suggested that religious beliefs helped individuals cope with their disease, find a sense of wellbeing, and help in the decision-making for their care and treatment [29]. It is also possible their belief would increase their emotional resilience [30], [31], [32]. Numerous studies reported the importance of religion and spirituality as patients' primary sources of the strength needed to cope with chronic and life-threatening diseases [33], [34], [35], [36].…”
Section: Discussionmentioning
confidence: 53%
“…It echoed previous research, which suggested that religious beliefs helped individuals cope with their disease, find a sense of wellbeing, and help in the decision-making for their care and treatment [29]. It is also possible their belief would increase their emotional resilience [30], [31], [32]. Numerous studies reported the importance of religion and spirituality as patients' primary sources of the strength needed to cope with chronic and life-threatening diseases [33], [34], [35], [36].…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, immigrant women in pain find themselves in the intersecting structure of ethnicity, class and gender that leads to multiple forms of isolation: at home, at work, socially and in clinical settings [ 26 , 43 ]. This may explain why immigrant women with chronic pain are more likely to be on longer sick leave than women without a migration background, to have depression, to use more painkillers, to experience more severe pain, and to have more pain sites than immigrant men [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, immigrant women in pain nd themselves in the intersecting structure of ethnicity, class and gender that leads to multiple forms of isolation: at home, at work, socially and in clinical settings (32,51). This may explain why immigrant women with chronic pain are more likely to be on longer sick leave than native women, to have depression, to use more painkillers, to experience more severe pain, and to have more pain sites than immigrant men (52).…”
Section: Immigrant Women In Painmentioning
confidence: 99%